Debates europeos sobre la justicia cultural y la interculturalidad / European debates about cultural justice and interculturality - GÓMEZ-MULLER, Alfredo (Utopía y Praxis Latinoamericana, 2020)
RESUMEN El artículo aborda algunos de los aspectos del debate distribución – reconocimiento a partir de los debates europeos de justicia cultural e interculturalidad. Se aboga por un modelo de mediación intercultural que permite mostrar la dinámica de estos procesos sociopolíticos en EEUU, Francia y Colombia, y propugna una revisión de la dialéctica entre universalismo y contextualismo que evite el esencialismo. Se concluye que la posibilidad de una mediación intercultural supone, en tanto condición primordial, ABSTRACT The article addresses some of the aspects of the distribution - recognition debate based on the European debates on cultural justice and interculturality. It advocates a model of intercultural mediation that allows to show the dynamics of these socio-political processes in the US, France and Colombia, and advocates a revision of the dialectic between universalism and contextualism that avoids essentialism. It is concluded that the possibility of intercultural mediation implies, as a fundamental condition, an aptitude to understand the other and to elaborate an "open" conception of culture and identity.